The Academic Administration Model Using Professional Learning Community in Small Primary Schools under the Office of the Basic Education Commission - Dumriwiset, Thattanya; Khuntharee, Naret; Singpan, Pongthorn (Ratchaphruek Journal, 2024)
The objectives of this research were to examine the current conditions and needs for the academic administration model using professional learning community, and to develop the academic administration model using professional learning community in small primary schools under the office of the basic education commission. The sample group were 240 educational administrators and academic teachers. The research instruments were questionnaire on current conditions and needs and model assessment form. The statistics were analyzed by mean and standard deviation. The results of the research revealed that the current conditions for the academic administration model using professional learning community in small primary schools are overall at a moderate level. The need to the academic administration model using professional learning community in small primary schools overall is at a highest level. The academic administration model should compose of 4 areas: The school curriculum development; The learning process development; The educational supervision; and The measurement and evaluation. Implemented using a professional learning community with 3 steps: 1) goal setting; 2) collaboration; and 3) reflection. The model is appropriate at the highest level and the overall possibility is at a high level.